Closing the achievement gap: from teacher education to student learning - Jesik, Shaynee L., author; Souder, Donna, advisor; Taylor, Ted, committee member; De Witt, Debra, committee member (Colorado State University. Libraries, 2013)
The academic achievement gap in the United States keeps growing every day. Beginning in eighth grade, students around the world are compared to each other using one international assessment to measure student performance. The results of the assessment are disheartening for Americans because American students rank among the lowest in the world when it comes to reading, math, and science. Because of the international assessment results, an academic sense of urgency has swept the nation. Legislation is currently writing and implementing new laws and bills to address the education epidemic spreading throughout the United States. All efforts are currently focusing on existing teachers and students in the classroom, as they should because that is where the current state of reality lies. However, everyone seems to overlook one very important contributor in educating students in grades kindergarten through twelfth. That contributor consists of the various teacher education programs within universities. These programs are responsible for preparing future teachers to educate 21st century learners. This research examines the current reality facing public education, discusses the possible reasons for the widening achievement gap in the United States, and offers possible solutions to cleansing and mending the systemic dysfunction found in education today. By exploring rhetoric and its place in teacher education programs and public education, the United States can begin to close the widening achievement gap.